Lipid Profile Response to Electroacupuncture in Non-Alcoholic Fatty Liver Patients with Hyperlipidemia - Mona Mohamed Taha; Abdelrhman Ismail Abdelghany; Ramy Salama Draz (Medical Association of Pharmacopuncture Institute, 2021)
Background : Non-alcoholic fatty liver disease (NAFLD) is estimated to be one of the most common diseases affecting the liver because of its high prevalence worldwide. Abnormal lipid profile between NAFLD patients has been reported in several studies. Objectives: This study aimed to evaluate the lipid profile response to electroacupuncture in NAFLD patients. Methods : A total of 60 female patients with NAFLD were included in the study with ages ranged from (30-55) years old. They were divided equally into two groups, group A received electroacupuncture (EA) stimulation at points of; LR14, LR3, ST36, and GB34. And group B received sham acupuncture application in non-acupuncture points. The demographic data and lipid profile such as total cholesterol (TC), serum triglycerides (TG), serum high-density lipoprotein (HDL), serum low-density lipoprotein (LDL) were recorded before and after the study. Results : The study results revealed a significant decrease (p < 0.05) of LDL, TC, TG after 6 weeks of non-interrupted treatment sessions in group A, However HDL showed no significant improvement (p > 0.05). A significant difference was found between posttreatment values of LDL, TC, and TG between both groups. Conclusion : Electroacupuncture can be an effective, simple, and applicable method for the improvement of elevated lipid profiles in NAFLD patients.